Tecticornia sp. (Samphire)—A Promising Underutilized Australian Indigenous Edible Halophyte - Srivarathan, Sukirtha; Phan, Anh Dao Thi; Hong, Hung Trieu; Chua, Elvis T.; Wright, Olivia; Sultanbawa, Yasmina; Netzel, Michael E. (Frontiers in Nutrition, 2021)
Salinization is gradually increasing over cropping soils and is challenging Governments in many countries, including Australia. There has been a high demand for utilizing arid and semi-arid land for sustainable food production. Currently, the main crops and forage plants are salt sensitive, while halophytes can tolerate a wide range of salinities. Samphire is an Australian indigenous edible halophyte and belongs to the genus Tecticornia. It is an underutilized, succulent plant growing on arid or semi-arid land. Most samphire species have a long history of use as food, but also as non-food (fodder and medicine), among indigenous communities in Australia, while scientific information is limited on their nutritional composition and potential bioactivity. The present study reports, for the first time, the nutritional composition, bioactive compounds (phytochemicals) and antioxidant capacity of six Australian grown samphire from different locations. The results showed that celosianin II and isocelosianin II could be identified as the predominant betalains (phytochemicals) in pigmented samphire species. Proximates and fibre varied significantly (p<0.05) between the samphire species with a highest value of fibre of 46.8 g/100 g dry weight (DW). Furthermore, samphire could be identified as a valuable source of essential minerals and trace elements, such as iron (41.5 mg/100 g DW), magnesium (1.1 g/100 g DW) and sodium (16.7 g/100 g DW). The fatty acid profile, mainly palmitic, stearic, oleic, linoleic and α-linolenic acid, was similar among the studied species. Total phenolic content and DPPH-radical scavenging capacity were different (p<0.05) between the six samphire samples. These initial results are very promising and indicate that Australian grown samphire may have the potential to be utilized as a functional food ingredient.